Intravenous administration of human amnion-derived mesenchymal stem cells improves gait and sensory function in mouse models of spinal cord injury - Tsuji, Shoichiro; Kuramoto, Yoji; Rajbhandari, Saujanya; Takeda, Yuki; Yamahara, Kenichi; Yoshimura, Shinichi (Frontiers in Cell and Developmental Biology, 2024)
Introduction Spinal cord injury (SCI) leads to severe disabilities and remains a significant social and economic challenge. Despite advances in medical research, there are still no effective treatments for SCI. Human amnion-derived mesenchymal stem cells (hAMSCs) have shown potential due to their anti-inflammatory and neuroprotective effects. This study evaluates the therapeutic potential of intravenously administered hAMSCs in SCI models. Methods Three days after induction of SCI with forceps calibrated with a 0.2 mm gap, hAMSCs or vehicle were administered intravenously. Up to 4 weeks of SCI induction, motor function was assessed by scores on the Basso Mouse Locomotor Scale (BMS) and the Basso-Beattie-Bresnahan Scale (BBB), and sensory function by hindlimb withdrawal reflex using von Frey filaments. Six weeks after SCI induction, gait function was assessed using three-dimensional motion analysis. Immunohistochemistry, polymerase chain reaction (PCR), flow cytometry, and ELISA assay were performed to clarify the mechanisms of functional improvement. Results The hAMSC treatment significantly improved sensory response and gait function. In the SCI site, immunohistochemistry showed a reduction in Iba1-positive cells and PCR revealed decreased TNFα and increased BDNF levels in the hAMSC-treated group. In assessing the systemic inflammatory response, hAMSC treatment reduced monocytic bone marrow-derived suppressor cells (M-MDSCs) and Ly6C-positive inflammatory macrophages in the bone marrow by flow cytometry and serum NO levels by ELISA assay. Discussion This study demonstrates the therapeutic potential of the hAMSC in SCI, with improvements in gait and sensory functions and reduced inflammation both locally and systemically. The findings support further investigation of the hAMSC as a potential treatment for SCI, focusing on their ability to modulate inflammation and promote neuroprotection.